The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4110/in.2010.10.6.219
|View full text |Cite
|
Sign up to set email alerts
|

NDRG2-mediated Modulation of SOCS3 and STAT3 Activity Inhibits IL-10 Production

Abstract: BackgroundN-myc downstream regulated gene 2 (NDRG2) is a member of the NDRG gene family. Our previous report indicated a possible role for NDRG2 in regulating the cytokine, interleukin-10 (IL-10), which is an important immunosuppressive cytokine. Several pathways, including p38-MAPK, NF-κB, and JAK/STAT, are used for IL-10 production, and the JAK/STAT pathway can be inhibited in a negative feedback loop by the inducible protein, SOCS3. In the present study, we investigated the effect of NDRG2 gene expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Our study did not focus on effects at the protein level, for example, the implication of the suppressor of cytokine signaling (SOCS) [33]. Additionally, this study was only performed in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not focus on effects at the protein level, for example, the implication of the suppressor of cytokine signaling (SOCS) [33]. Additionally, this study was only performed in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, STAT-3 silencing found to reduce IL-10 expression significantly, while SOCS3 silencing induced [28]. Recently, NRDG2 (N-myc downstream regulated gene 2) expression has been shown to modulate SOCS3 and STAT-3 activity, eventually leading to inhibition of IL-10 production [29]. Signaling mechanism particularly MAPkinase pathways involved in anti-inflammatory action of IL-10 is reviewed by Haddad et al [30].…”
Section: Introductionmentioning
confidence: 97%
“…Two human cDNAs, encoding NDRG3 and NDRG4, are homologous to NDRG1. These two genes, together with NDRG1 and a previously deposited cDNA (designated NDRG2), constitute the NDRG gene family [17]. Previous studies reported that NDRG2 was associated with human lung cancer, and the decreased expression of NDRG2 was correlated with a worse outcome of lung cancer patients [12,18].…”
Section: Discussionmentioning
confidence: 99%